PENGEMBANGAN GAME JEGOG BERBASIS ANDROID - Wija Antara, I Gede; Mahendra Darmawiguna, I Gede; Gede Sunarya, I Made (Universitas Pendidikan Ganesha, 2014)
Gamelan Jegog is one of thetraditional instrument which originally comesfrom Bali. Each Jegog’s instrument consists ofeight piece of bamboo with each piece is called as